CONTEMPORARY ASPECTS OF PHYSICAL THERAPY FOR PATIENTS WITH MULTIPLE SCLEROSIS FROM THE EVIDENCE-BASED PRACTICE PERSPECTIVE - Павлова, Тетяна; Мерзлий, Микола (SWorldJournal, 2026)
The article summarizes contemporary approaches to physical therapy for patients with multiple sclerosis from the perspective of evidence-based practice. The findings of systematic reviews, meta-analyses, and clinical guidelines regarding the effectiveness